The Role of Information System Effectiveness in Strengthening Financial Management and Performance Evaluation - Syaifuddin, Syaifuddin (International Journal of Economics (IJEC), 2026)
Digitalisation in the public sector has led to higher demands for transparency, accountability, and accurate reporting. However, many organisations still face obstacles such as unsynchronised data, slow reporting processes, and performance evaluations that are not fully evidence-based. These conditions indicate that the effectiveness of information systems is urgently needed to strengthen organisational governance and performance. This study aims to analyse the influence of Information System Effectiveness on Financial Governance and Performance Evaluation in Regional Apparatus Organisations (OPD) within local government. The study uses a quantitative approach with an explanatory research design. The research population consists of OPD employees involved in the use of information systems, financial management, and/or performance evaluation. The sampling technique used purposive sampling with a sample size of 120 respondents. Data collection was conducted through questionnaires in the period November–December 2025. Data analysis used PLS-SEM with the help of SmartPLS through measurement model and structural model evaluation. The results showed that information system effectiveness had a positive effect on strengthening financial governance and improving performance evaluation. These findings confirm that an effective information system not only serves an administrative function but also becomes a strategic factor in ensuring more transparent financial management and more objective performance assessment. The implications of this study encourage OPDs to prioritise improving system quality, data integration, and information utilisation as a basis for performance control and evaluation.